The Effect of Ticket Prices and Service Quality on Consumer Satisfaction and Customer Loyalty (Air Transport Literature Review) - Fikri Al-Kautsar, Muhammad (Dinasti Publisher, 2022)
Literature Review Article The Effect of Accuracy of Flight Schedules, Ticket Prices and Service Quality on Consumer Customer Satisfaction (Air Transport Literature) is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Financial Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are: 1) Knowing the effect of flight ticket prices on consumer satisfaction; 2) Knowing the effect of the quality of flight services on customer satisfaction; 3) Knowing the effect of flight ticket prices on customer loyalty; 4) Knowing the effect of the quality of airline services on customer loyalty; and 5) Knowing the impact of customer satisfaction on customer loyalty